Konseling Interpersonal dalam Menumbuhkan Kesehatan Mental Korban Bullying - Rahma, Allya; Istima, Fatan; Addinullah, Moh Aziz; Nihayah, Ulin (Nosipakabelo: Jurnal Bimbingan dan Konseling Islam, 2022)
Bullying is an act of aggression committed by someone ora group of people committed against another person and committed repeatedly to harm others physically and mentally. Bullying can affect others who feel harassed, bullied, feared, and without the power to fight the perpetrator. Bullying behavior is divided into a variety of physical bullying, verbal bullying, online bullying, and even cyberbullying. Bullying may occur because of such factors as ward factors, family factors, behavior or personality factors, and the role of peers. Research methods used to write this journal are studies of literature based on case studies. Analysis reveals that the effects of bullying, affecting mental health, and this can be counseled behavior and interpersonal realities to prevent the disparity caused by bullying.